Place and role of «Seljuk Name» in the cultural heritage Kazakhstan and Central Asia - Жумaдиловa, Г. Т. (Journal of Oriental Studies, 2018)
Seljukname” in the cultural heritage of Kazakhstan and Central Asia is an urgent scientific task, primarily because of the need to explore the basic socio-economic and political processes in the countries of this region on the basis of historical and cultural source. Monuments are the link between generations through the preservation and augmentation of the traditions and distinctive cultural values. Study on cultural heritage through the prism of historical sources in our time is important.